Embryo Cryopreservation as an Alternative to Treat Infertility in Breast Cancer Survivors in Reproductive Age: Case Reports - Dwirani Rosmala Pratiwi; Noer Halimatus Syakdiyah; Ario Djatmiko; Lia Natalia Hinting (Indonesian Journal of Cancer, 2022)
Introduction: Chemotherapy has been shown to reduce breast cancer (BC) mortality significantly. However, several types of chemotherapy drugs affect the reproductive system. As BC has become increasingly prevalent, many young women are diagnosed during their reproductive years. As a result, overcoming chemotherapy-related infertility is becoming increasingly important. Hence, in-vitro fertilization (IVF) with embryo cryopreservation before chemotherapy is considered a way to preserve future reproductive potential. For this reason, this paper aims to report the cases of safe pregnancy in BC survivors through pre-chemotherapy IVF followed by embryo cryopreservation.Case Presentation: Two women, aged 35 and 29, respectively, were treated for BC by surgery, chemotherapy, and tamoxifen. They performed in-vitro fertilization (IVF) with embryo cryopreservation before chemotherapy. Their pregnancy was completed without complications, and they gave birth to healthy babies. Their last oncological visit also showed no signs of cancer recurrence, showing disease-free intervals of seven and eight years, respectively.Conclusions: Pre-chemotherapy IVF followed by embryo cryopreservation can be an alternative to treat infertility in BC survivors of reproductive age who are receiving chemotherapy.